Компьютерная ранняя диагностика сахарного диабета методами математического моделирования - Лапта, С. С.; Поспелов, Л. А.; Соловьёва, О. И. (НТУ "ХПИ", 2014)
В статье рассмотрена проблема повышения качества ранней диагностики сахарного диабета, выявления предшествующих ему состояний с нарушенной толерантностью к глюкозе. Предлагается новая система компьютерной ранней диагностики сахарного диабета на основе математического моделирования динамики гликемии и параметрической идентификации модели для обследуемого пациента по клиническим данным проведенного у него перорального теста толерантности к глюкозе. Ее преимущество в возможности выявления латентных форм СД перед действующей официальной системой Всемирной организации здравоохранения установлено статистически достоверно.

The paper considers the problem of improving the quality of early diagnosis of diabetes, identifying antecedent conditions with impaired glucose tolerance. On the basis of the parameters of the glycemic dynamics mathematical model, individualized for a tested patient according to clinical data of his oral glucose tolerance test, the system of computer early diagnostics of Diabetes mellitus was constructed. It was statistically demonstrated it’s advantages over the working official World Organization of Health system in possibility of diabetes mellitus latent forms revealing. The values of the model parameters of the dynamics of glycemia almost uniquely determine the nature and type of the glycemic curve glucose tolerance test. they are integral status information system of regulation of carbohydrate metabolism and may therefore be use d for its overall diagnosis. For individualization of blood glucose dynamics model were used glycemic patient data obtained in the Institute of Medical Sciences of Ukraine endocrine pathology.
Computer early diagnostics of the Diabetes mellitus by the methods of mathematical modelling
Keywords: система диагностики; дифференциальное уравнение; system of diagnostics; diabetes mellitus; mathematical model; differential equalization